2012
DOI: 10.1128/aem.06991-11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Linuron HydrolaselibAGene Pool Size in Response to Linuron Application and Environmental Perturbations in Agricultural Soil and On-Farm Biopurification Systems

Abstract: ABSTRACTlibA, a gene encoding a novel type of linuron hydrolase, was recently identified in the linuron-mineralizingVariovoraxsp. strain SRS16. In order to assess the contribution oflibAto linuron degradation in environmental settings,libAabundance was monitored in response to the application of linuron and to environmental pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…hylA gene copy numbers did not respond on linuron application in BMs containing nonprimed soil, indicating that hylA-carrying microorganisms likely originate from soil L, which was included in the BM matrix, indicating a successful invasion of hylA linuron-degrading bacteria from that primed soil in the overall system. The same was concluded for libA (21). As with libA, hylA abundance appears to correlate with the observed dynamics of the linuron mineralization capacity in the system containing primed soil, i.e., hylA gene copy numbers were relatively high and low when the linuron mineralization capacity was high and low, respectively (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…hylA gene copy numbers did not respond on linuron application in BMs containing nonprimed soil, indicating that hylA-carrying microorganisms likely originate from soil L, which was included in the BM matrix, indicating a successful invasion of hylA linuron-degrading bacteria from that primed soil in the overall system. The same was concluded for libA (21). As with libA, hylA abundance appears to correlate with the observed dynamics of the linuron mineralization capacity in the system containing primed soil, i.e., hylA gene copy numbers were relatively high and low when the linuron mineralization capacity was high and low, respectively (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…libA gene copy numbers, 16S rRNA gene copy numbers, and linuron mineralization capacity data used in this study were taken from previous reports (9,16,20,21). The lag times determined in the linuron mineralization kinetics recorded in linuron mineralization assays using samples taken from the field or SM and BM experiments as inoculum were used as a measure for the linuron mineralization capacity, i.e., the shorter the lag phase, the higher the mineralization capacity (9,16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPS act like biofilters in which the filter matrix (biomix) is composed of a mixture of different adsorbing materials, such as peat, straw, and topsoil (2), and contain microorganisms carrying mobile genetic elements (MGEs) that harbor genes involved in biodegradation of xenobiotic compounds (3,37). Although it is well known that biodegradation is the main process in the removal of xenobiotic compounds from the environment (3), abiotic factors such as temperature and concentration of pesticides can substantially influence their degradation (4).…”
mentioning
confidence: 99%
“…In the past, ecological studies showed that the dynamics of linuron-degrading activity in the environment as a response to linuron application (i.e., in linuron-treated agricultural soil and on-farm biopurification systems), is not always explained by the abundance of libA (26). We are currently investigating whether hylA provides an alternative explanation in those case studies, whether organisms containing hylA or libA coexist or compete in linuron-treated and -contaminated environments, and whether still other linuron hydrolysis gene functions exist.…”
Section: Discussionmentioning
confidence: 99%